Exploring the Digital Space in Investigating the Gender Representation of Indonesian Professional Accountant Institutions - Qonita; Satia Nur Maharani; Sri Pujiningsih (PENANOMICS: International Journal of Economics, 2023)
This study aims to determine and analyze how gender representation is framed from media positions, subject-objects, and readers' positions based on Critical Discourse Analysis Sara Mills. The preparation of the writing of this research uses a critical paradigm qualitative method. Data were retrieved from the website and online news from the Financial Services Authority, which focuses on programs segmented by women, for data collection in this study using participant observation or independent people as data validity by analyzing how the gender representation of professional accounting institutions is displayed based on Sara Mills' Critical Discourse Analysis. The research findings show that the subject's position in the discourse is presented as a female figure who is educated, successful in the public sphere, and can positively influence society. However, the representation of women in other programs is still low and is dominated by men.